a hypothoses is a proven fact, true or false?

FALSE. A hypothesis can not be proven true unless a highly recognized scientist does an experiment to find evidence that the hypothesis can be supported.

Expert answered|jher000|Points 7720|

Question

Asked 10/15/2012 11:40:43 AM

0 Answers/Comments

This answer has been confirmed as correct and helpful.

s

Rating

There are no new answers.

Simplify n - {1 - [n - (1 - n) - 1]}.
n - 1
-n - 1
3n - 3
-3n + 3 **Weegy:** {n - 1 - [n - 1 - (n - 1)]} = (a)n - 1 **User:** Simplify {n - 1 - [n - 1 - (n - 1)]}.
n - 1
-n - 1
3n - 3
-3n + 3 **Weegy:** {n - 1 - [n - 1 - (n - 1)]} = (a)n - 1 **User:** Simplify n - {1 - [n - (1 - n) - 1]}.
n - 1
-n - 1
3n - 3
-3n + 3 **Weegy:** n - {1 - [n - (1 - n) - 1]} = (c) 3n - 3 **User:** Given: Q = 7m + 3n, R = 11 - 2m, S = n + 5, and T = -m - 3n + 8.
Simplify [Q - R] + [S - T] **Weegy:** substitute the corresponding expression for each letter (keep the operation sign!) and simplify - > 9) Q+S-T - > (7m+3n)+(n+5)-(m-3n+8)
**User:** (7m+3n)+(n+5)-(m-3n+8) **Weegy:**
= 7m + 3n - (11-2m+n+5) + m + 3n - 8
= 7m + 3n - 11 + 2m - n - 5 + m + 3n - 8
= 10m + 5n -24
**User:** Given: Q = 7m + 3n, R = 11 - 2m, S = n + 5, and T = -m - 3n + 8.
Simplify Q - [R + S] - T. (More)

Question

Expert Answered

Updated 9/22/2014 5:51:15 AM

4 Answers/Comments

Q = 7m + 3n, R = 11 - 2m, S = n + 5, and T = -m - 3n + 8.

[Q - R] + [S - T]

= 7m + 3n - 11 + 2m + n + 5 + m + 3n - 8

= 9m + 4n - 6 + m + 3n - 8

= 10m + 7n - 14

[Q - R] + [S - T]

= 7m + 3n - 11 + 2m + n + 5 + m + 3n - 8

= 9m + 4n - 6 + m + 3n - 8

= 10m + 7n - 14

Added 9/22/2014 5:49:17 AM

(7m+3n)+(n+5)-(m-3n+8)

= 7m + 4n + 5 - m + 3n - 8

= 6m + 7n - 3

= 7m + 4n + 5 - m + 3n - 8

= 6m + 7n - 3

Added 9/22/2014 5:50:42 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [9/22/2014 7:01:50 AM]

Simplify a - {b - [c - (d - e) - f] - g}.
a + b + c - d + e - f + g
a - b + c - d + e - f + g
a + b + c + d + e - f + g
a - b + c - d + e + f - g **Weegy:** The correct response to this problem is answer (d) a - b + c - d + e + f - g **User:** Take 2y2 - 3y - 5 from y3 - 6y2 + 5y. Select the correct answer.
y3- 2y2+ 3y+ 5
y3- 4y2+ 2y- 5
y3- 4y2+ 2y+ 5
y3- 8y2+ 8y+ 5 **Weegy:** ((y+1)(2y-5))/(y(y-1)(y-5)) is the answer that I get. Is there another option/answer that you accidentally omitted when you asked this question? (More)

Question

Expert Answered

Updated 6/16/2014 7:41:30 AM

1 Answer/Comment

33,152,976

questions answered

There are no comments.